Clinicopathological features and surgical options for synchronous colorectal cancer. Issue 9 (March 2017) - Lee, Byoung Chul; Yu, Chang Sik; Kim, Jihun; Lee, Jong Lyul; Kim, Chan Wook; Yoon, Yong Sik; Park, In Ja; Lim, Seok-Byung; Kim, Jin Cheon
Abstract : Abstract: This study was conducted to investigate the clinicopathological features of synchronous cancers and treatment options according to their locations. Records of 8368 patients with colorectal cancer treated at our center between July 2003 and December 2010 were analyzed retrospectively. All synchronous colorectal cancer patients who underwent surgical treatment were included. Synchronous cancers were identified in 217 patients (2.6%). Seventy-nine patients underwent either total colectomy, subtotal colectomy, or total proctocolectomy; 116 underwent 1 regional resection, including local excision; and 22 underwent 2 regional resections. The mean age was 62 years, slightly higher than that for the single-cancer patients. Synchronous cancers were more common in male patients, more frequently located in the left colon, had more microsatellite instability-high status, and showed more advanced stage than single cancer. Extensive resection was mainly performed for synchronous cancers located in both the right and left colon. Two regional resections were performed for cancers in the right colon and rectum. There were no differences in complication rates or the occurrence of metachronous cancer between the 2-region resection and extensive resection groups. Eight years postoperatively, the mean number of daily bowel movements for these 2 groups were 1.9 and 4.3, respectively. We found that synchronous cancer was different from single cancer in terms of age, gender, location, and pathologic features. Synchronous colorectal cancer requires different treatment strategy according to the distribution of lesions. Comparison between the 2 regional resections and extensive resection approaches suggests that 2 regional resections are preferable.